The introduction of credit-module and module-rating technology education in Ukraine - RIDEY, Natalia; PALAMARCHUCK, Svetlana; SHOFOLOV, Denis (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
In the article the analysis of the introduction of credit-modular and modularrankingtechnology education in Ukraine and worldwide. Established consistentcredit rating modular training and evaluation in the implementation of of theEuropean Credit Transfer System in Ukraine